2001
DOI: 10.1007/s004640090032
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and humoral inflammatory response after laparoscopic and conventional colorectal resections

Abstract: Postoperative cell-mediated immunity was better preserved after laparoscopic than after conventional colorectal resection. Cellular cytokine production was preserved only in the laparoscopic group, while cytokine plasma levels were significantly higher in the conventional group. These findings may have important implications for the use of laparoscopic colorectal resection, especially in patients with malignant disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
146
3
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(170 citation statements)
references
References 29 publications
14
146
3
7
Order By: Relevance
“…The vast majority of surgery-related blood protein alterations are short-lived with a duration of 6 h to 5 days, as is the case for CRP, IL-6, IL-2, EGF, HGF, IGFBP-3 and others (28)(29)(30). Most of the short duration blood compositional changes are related to the acute phase inflammatory response to surgical trauma and anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of surgery-related blood protein alterations are short-lived with a duration of 6 h to 5 days, as is the case for CRP, IL-6, IL-2, EGF, HGF, IGFBP-3 and others (28)(29)(30). Most of the short duration blood compositional changes are related to the acute phase inflammatory response to surgical trauma and anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…assisted comparison) but not for the rest of the 1st month after surgery is consistent with there being a different early mechanism. A likely candidate is the short-lived acute inflammatory response that occurs after major surgery and has been shown to directly correlate with incisional length (29,30). Perhaps after the acute response the healing wounds are the principal source of the added IL-8 in the blood stream.…”
Section: Discussionmentioning
confidence: 99%
“…Key words: Interleukin (IL)-6 -Cytokine -Peritoneal fluid -Surgical stress -Gastric cancerLaparoscopic surgery -Gastrectomy R ecent advances in laparoscopy techniques have heralded a new era in the field of abdominal surgery, and laparoscopic approaches are now being employed for the treatment of malignant neoplasms of the stomach, colon and other organs. [1][2][3][4][5] It has been reported that levels of circulating proinflammatory cytokines such as interleukin (IL)-1 beta, IL-6, IL-8, and tumor necrosis factor (TNF)-alpha are related to the extent and severity of surgical procedures.6-8 Interleukin 6 is a sensitive and early marker of tissue damage, and in general the greater the surgical trauma, the greater the response of Many studies have shown that the level of IL-6, as an indicator of surgical stress, is significantly lower after laparoscopic surgery than after open surgery.9-15 Most of the studies reported so far have measured and analyzed the concentration of IL-6 in plasma or serum, 9,10,[12][13][14][15][16]18 and only rarely in peritoneal fluid, 11,12,15,17,19,20 and the results have indicated significant correlations between the level of IL-6 and several clinical parameters. However, there is some concern as to whether the concentration of IL-6 in peritoneal fluid adequately reflects the degree of surgical stress.…”
mentioning
confidence: 99%
“…Even if uncommon in healthy patients (LE 1b) [379], a ventilation-perfusion mismatch may also occur, sometimes resulting in perioperative hypoxemia (LE 1b) [380][381][382]; (LE 2a) [383]. A decrease in lung volume associated with airway (P aw ) and intra-abdominal pressure (IAP) increases may lead to lung atelectasis, mainly in patients with extensive pulmonary disease (LE 1b) [364,376].…”
Section: Pathophysiological Changes During Laparoscopymentioning
confidence: 99%